Biochemical, electrophysiological and immunological characterization of the venom from Centruroides baergi, a new scorpion species of medical importance in Mexico. (September 2020) - Gómez-Ramírez, Ilse V.; Riaño-Umbarila, Lidia; Olamendi-Portugal, Timoteo; Restano-Cassulini, Rita; Possani, Lourival D.; Becerril, Baltazar
Abstract: In this communication the isolation, chemical and physiological characterization of three new toxins from the scorpion Centruroides baergi are reported. Their immunoreactive properties with scFvs generated in our group are described. The three new peptides, named Cb1, Cb2 and Cb3 affect voltage-dependent Na + channels in a differential manner. These characteristics, explain the toxicity of this venom. Molecular interactions in real-time among these toxins and the best recombinant antibodies generated in our group, revealed that one of them was able to neutralize the main toxin of this venom (Cb1). These results represent an important advance for the neutralization of this venom and serve as the basis for generating new scFvs that will allow the neutralization of similar toxins from other venoms that have no yet been neutralized. Highlights: Identification of scorpion toxins allows the generation of new neutralizing agents. Three toxic components to mammals were found in Centruroides baergi venom. Cb1, Cb2 and Cb3 affect differentially human sodium channels. The most abundant toxin, Cb1, was totally neutralized.